Pengaruh Pendidikan Kesehatan Tentang Pijat Bayi Terhadap Perilaku Ibu Dalam Memijat Bayi Secara Mandiri Di KelurahanGirimargo Sragen - Baroo'ah, Butsainatul; , Siti Arifah, S.Kp., M.Kes; , Wachidah Yuniartika, S.Kep., Ns (2015)
Infant massage is a form of alternative medicine that is becoming increasingly popular because of its simplicity, cost-effectiveness, easy to learn and can be done at home by the family, but many mothers can't do baby massage independently. The purpose of this study was to determine the effect of health education about infant massage to the mother's behavior in baby massage independently in Girimargo District of Sragen. The research method is pre experiment with the design of one group pre test post test desaign. Samples are 21 respondents using cluster sampling. Data collection techniques with observation sheet for 7 days. Data were analyzed by Wilcoxon Rank Test. Wilcoxon test analysis results ρ = 0.000 (ρ <0.05), it was concluded the influence of health education about infant massage to the mother's behavior in baby massage independently in Girimargo District of Sragen.